Child Protection Affected by the Covid-19 in Indonesia: Islamic Perspective - putri, suci ramadhani (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This article is a library research from textual analysis related to child protection from the perspective of Islamic regulation and Covid-19. The data analysis method is qualitative-descriptive analysis method. The description of the data is divided into several stages, namely: Islam and the Covid-19 in Indonesia, Children in Islamic point of view, National Movement for Foster Parents or Gerakan Nasional Orang Tua Asuh (GNOTA), and Child Protection Affected by the Covid-19 from Islamic Perspective. The study shows children as one of the groups who are vulnerable to get their rights lost due to the Covid-19 pandemic, such as the right to life, economy, education and others. In Islamic regulation, childrenâ€™s rights (ri'ayah) are contained in maqÄshid sharia, namely maintaining children (hifÅ¼ al-nasl). Responding to the absence of regulatory certainty in Indonesia that protects the rights of children affected by the Covid-19 pandemic, even though Islam protects children through the value of hifÅ¼ al-nasl, the presence of the Gerakan Nasional Orang Tua Asuh is expected to be an alternative solution to protect children affected by the Covid-19 pandemic in Indonesia.Artikel ini merupakan penelitian kepustakaan dengan sumber data penelitian bersumber dari literatur terkait perlindungan anak perspektif hukum Islam dan Covid-19. Metode analisis data yang digunakan yaitu metode analisis kualitatif-deskriptif. Deskripsi data terbagi ke dalam beberapa tahapan, yaitu: Islam dan Pandemi Covid-19 di Indonesia, Anak dalam pandangan hukum Islam, Mengenal Gerakan Nasional Orang Tua Asuh (GNOTA), dan Perlindungan Anak Terdampak Pandemi Covid-19 Perspektif Hukum Islam. Hasil penelitian ini adalah bahwa anak menjadi salah satu kelompok yang rentan terenggut hak-haknya akibat pandemi Covid-19, seperti hakhidup, ekonomi, pendidikan dan lainnya. Di dalam hukum Islam, merawat dan memenuhi hak-hak anak (riâ€™ayah) merupakan salah satu makna yang juga terkandung dalam maqÄshid syariah, yakni menjaga keturunan (á¸¥ifÅ¼ al-nasl). Menyikapi belum adanya kepastian regulasi di Indonesia yang melindungi hak-hak anak terdampak pandemi Covid-19, padahal Islam melindungi anak melalui nilai á¸¥ifÅ¼ al-nasl, maka kehadiran Gerakan Nasional Orang Tua Asuh (GNOTA) diharapkan dapat menjadi solusi alternatif untuk melindungi anak-anak terdampak Pandemi Covid-19 di Indonesia.